CONTRASTIVE ANALYSIS OF THE CONCEPT PARENTS IN ENGLISH AND UZBEK LANGUAGES - Khayitova Shohida Erkin Qizi (PEDAGOGS, 2024)
Annotation: The current state of scientific development of topical problems of linguistics, the tasks of lexicology, the prospects for the general development of the theory of meaning and evaluation necessitate the search for linguistic innovations, a new look at previous problems and involve many questions that have not been studied comparatively in the orbit of scientific research in linguistics.